2014
DOI: 10.1159/000369587
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of the Added Value of Imaging within the Dutch National Diagnostic Appendicitis Guideline - Do we Forget our Clinical Eye?

Abstract: Background: Annually 16,000 appendectomies are performed in the Netherlands, of which 15-20% are negative. In 2010, to reduce this unacceptable percentage of superfluous appendectomies, the Dutch Association for Surgery introduced the ‘Appendicitis Guideline'. This guideline recommends the use of imaging. In this observational prospective study the added value of imaging in everyday clinical practice is evaluated. Methods: All patients with suspected appendicitis were included at the emergency department of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…An increased proportion of uncomplicated cases could have indicated the overuse of surgery when additional radiology was used but this outcome was not found in our study. Other studies have also demonstrated 151 a decrease in the number of negative appendectomies with increased use of preoperative imaging [18,28,29]. An important benefit of reducing the number of negative appendectomies is avoiding complications from unnecessary surgery, which according to our data are comparable in number to that of OA.…”
Section: Discussionsupporting
confidence: 70%
“…An increased proportion of uncomplicated cases could have indicated the overuse of surgery when additional radiology was used but this outcome was not found in our study. Other studies have also demonstrated 151 a decrease in the number of negative appendectomies with increased use of preoperative imaging [18,28,29]. An important benefit of reducing the number of negative appendectomies is avoiding complications from unnecessary surgery, which according to our data are comparable in number to that of OA.…”
Section: Discussionsupporting
confidence: 70%
“…This leads to an enormous increase in costs purely for diagnosing appendicitis acuta. In the previously mentioned prospective study that was carried out in our hospital, it was found that computed tomography also sometimes gave false positive results in patients suspected of acute appendicitis (9). Although we were a little sceptical to increase the use of imaging for diagnosing acute appendicitis, as was proposed by the new guideline that was released in February 2010, our data show a significant decline in negative appendectomies.…”
Section: Discussionmentioning
confidence: 50%
“…The most common misdiagnosis among men was diverticulitis of the colon. 7 Although in some studies, preoperative US and CT scan lower rates of negative appendectomy were reported, the results of the studies by Papes et al 8 and Schok et al 9 formed the opinion that diagnosis of appendicitis should still mainly be based on history, and clinical and laboratory data. 8 The study by Webb et al has shown that NAR was decreased for adult patients who underwent preoperative CT scan compared with patients with the lack of preoperative imaging.…”
mentioning
confidence: 99%